White wines aged in barrels with controlled tannin potential exhibit correlated long-term oxidative stability in bottle - Kevin Billet; Cécile Thibon; Marie Laure Badet; Nolwenn Wirgot; Laurence Noret; Maria Nikolantonaki; Regis D. Gougeon (Food Chemistry: X)
Chardonnay and Sauvignon blanc wines aged in oak wood barrels with low and medium tannin potentials were discriminated for their abilities to resist against oxidation during bottle storage. The oak wood tannin potential was positively correlated to wines antioxidant capacity after 2 and 4 years of bottle aging. Untargeted molecular analysis revealed that the Sauvignon blanc metabolome was more affected by the tannin potential than the Chardonnay. Supervised statistical analysis highlighted the extensive oak wood contribution to the wine chemical fingerprints. Wines aged in barrel of medium tannin potential were associated with higher concentrations in antioxidant compounds such as dipeptides. Moreover, quantitative differences were observed between oak barrel derived volatile compounds. Sauvignon blanc volatile thiols appeared to decrease during bottle aging, regardless of the oak tannin potential. This study highlights the post bottling positive impact of oak wood barrel aging on wines oxidative stability, related to oak barrel tannin potential.